Post vasectomy chronic pain: are we under diagnosing vasitis? A case report and review of the literature. (4th December 2020) - Jones, Adam; Vazirian-Zadeh, Mahmood; Phan, Yih Chyn; Mahmalji, Wasim
Abstract: Acute vasitis is a rare infection of the vas deferens. Clinical presentation and disease rarity can cause difficulty in correctly diagnosing this condition. Adjuncts to aid diagnosis can be used that include ultrasound scan (USS) or computed tomography. We report a unique case of acute vasitis following vasectomy, reversal and subsequent re-do vasectomy diagnosed using USS.